Empresas de controle familiar e informed trading: evidências de short selling no mercado brasileiro? - Ujikawa, Carolina Miyuki (2015)
The aim of this study is to test whether, in the Brazilian market, family firms are more susceptible to insider trading. Tests done in US market demonstrated the effect of family control in informational content of short sales in publicly-traded companies. There, had found higher than normal levels of short sales in family controlled companies, mainly in times that anticipated negative earnings announcements. We did not find clear evidence that the fact that the company has family control could take it to submit or not insider trading, since for limitation of the model is not possible to compare the abnormal level of short sales for family-controlled companies and others, since this variable it is removed from the model. However, we observed in the fixed panel models with interactions that there are differences in the effect of some control variables for family-controlled companies or not on other variables of control, which could show that some influence the parental control could have on insider trading. We also tested whether state-controlled companies show more abnormal average daily short sales in moments that precede earnings surprises, and we did not find clear and direct evidence that this happened.